Assessing the Cause of Prenatal Mortality in Medical Centers of Alborz Province - Sara Esmaelzadehsaeieh; Ehsan Zahmatkesh; Mitra Rahimzadeh; Nastaran Azami (Guilan University of Medical Sciences, 2016)
Background: Prenatal mortality is important indicator of health and health care services at birth, therefore understanding the major prenatal mortality causes will help the society to plan better prenatal and neonatal care system. Objective: This study aimed to determine the causes of Prenatal Mortality in Medical Centers of Alborz Province Methods: This was a retrospective study conducted on 446 cases of intrauterine and neonatal deaths in 2012 which occurred in Medical Centers of Alborz Province and was recorded by relevant authorities in the application INFO PATH. Data were analyzed using descriptive statistics, chi-square test. Result: 324 cases (72.6%) died in the uterus and 122 cases (27.4%) of neonate died after birth from 44.6 cases intrauterine and neonatal deaths, most time elapse of death was 50 hours after birth. 101 cases (24%) of death at birth was due to congenital abnormality and 62 patients (61.4%) were in the group of intrauterine deaths and 39 cases (38.6%) in the group of death 30 days after delivery. The most common congenital abnormality was neural tube defects (15.2%). 57 (12.8 %) mothers had disease and diabetes was the most prevalent (3.8%). By category (ICD10) in this study, the highest rate of fetal death in 359 cases (805%) were in a group of disorders with unknown origin and 186 cases (40.6%) of this group were in sub group of related disorders of duration of pregnancy and fetal growth and premature delivery was the most complication of pregnancy. Conclusion: Prenatal mortality rate in this study was 11.5 in 1000 live birth. Result of present study showed that most of intrauterine fetal death causes were preterm delivery and unknown death. Therefore, in addition to health needs, identifying the causes of preterm labor and its related factors are also recommended. In this study, none of the causes of death had been determined by autopsy. Autopsy of death due to unknown causes is also recommended so that better and more proper intervention can be taken to prevent intrauterine deaths